Monitoring of Hadrontherapy Treatments by Means of Charged Particle Detection - Muraro, Silvia; Battistoni, Giuseppe; Collamati, Francesco; De Lucia, Erika; Faccini, Riccardo; Ferroni, Fernando; Fiore, Salvatore; Frallicciardi, Paola; Marafini, Michela; Mattei, Ilaria; Morganti, Silvio; Paramatti, Riccardo; et al. (Frontiers in Oncology, 2016)
The interaction of the incoming beam radiation with the patient body in hadrontherapy treatments produces secondary charged and neutral particles, whose detection can be used for monitoring purposes and to perform an on-line check of beam particle range. Charged particles are potentially attractive since they can be easily tracked with a high efficiency, in presence of a relatively low background contamination. In order to verify the possibility of exploiting this approach for in-beam monitoring in hadrontherapy, and to guide the design of specific detectors, both simulations and experimental tests are being performed with ion beams impinging on simple homogeneous tissue-like targets (PMMA). An important outcome of these studies is that the experimental single track resolution needed for charged particle based monitoring applications can be safely of the order of few millimeters, without spoiling the precision achievable on longitudinal shape. The results obtained so far show that the measurement of charged particles can be successfully implemented in a technology capable of monitoring the dose profile and the position of the Bragg peak inside the target and finally lead to the design of a novel profile detector. Crucial aspects to be considered are the detector positioning, to be optimized in order to maximize the available statistics, and the capability of accounting for the multiple scattering interactions undergone by the charged fragments along their exit path from the patient body. The experimental results collected up to now are also valuable for the validation of Monte Carlo simulation software tools and their implementation in Treatment Planning Software packages.